"The relevance of the organization's entrepreneurial leader" Case Study - Automobile sector in the municipality of Vila Nova de Famalicão (Revista Lusófona de Economia e Gestão das Organizações, 2016)
ABSTRACT Entrepreneurship is a concept increasingly present in business organizations or in educational systems, assuming an incremental prominence in public debate regarding the future of economic policies for competitiveness within the knowledge economy and information society. Its relevance prompted the study in its various aspects, worsened by the structural crisis of capital. The privileged behavioral analysis of the entrepreneur's profile and identification of its role in organizations was supported by a case study on the automotive companies in Portugal, Vila Nova Famalicão. It states a close relationship between the entrepreneurship concept and the fruitful discovery of opportunities, which are based on spirit of change and innovation, central to the entrepreneur. Competitiveness appears as a basic premise in value creation and sustainable progress of organizations. The study also allowed confirming a dissimilarity of concepts and approaches, grounded in empirical and scientific evidence that is still exiguous. The work thus aimed to raise awareness of organizational and academic communities to this issue, contributing to a more comprehensive and current understanding of its relevance within the organizations. The multidimensional paradigm change occurs in a structurally weakened economic and financial situational context, which instigates a transfiguration of the concepts and patterns observed until now. Entrepreneurship and the behavioral profile of the entrepreneurial leader are of paramount importance in the effective value creation process: incremental, distinctive and sustainable.     Keywords: Entrepreneur profile, organizational performance, sustainability, innovation, opportunity.   RESUMO O empreendedorismo é um conceito cada vez mais presente nas organizações empresariais ou nos sistemas educacionais, assumindo um destaque incremental no debate público no que concerne ao futuro das políticas económicas para a competitividade, no âmbito da economia do conhecimento e da sociedade da informação. A sua pertinência instigou o estudo nas suas diversas valências, agudizado pela crise estrutural do capital. A análise privilegiadamente comportamental do perfil do empreendedor e a identificação do seu papel nas organizações foi corroborada por um estudo de caso sobre empresas do ramo automóvel em Portugal, Vila Nova Famalicão. Anui-se uma relação estreita entre o conceito de empreender e a descoberta profícua de oportunidades, que se fundeiam num espírito de mudança e inovação, central ao empreendedor. A competitividade afigura-se como premissa basilar na criação de valor e no progresso sustentável das organizações. O estudo permitiu atestar também uma dissimilitude de conceitos e aceções, alicerçados em evidências empíricas e científicas ainda exíguas. O trabalho objetivou assim uma maior sensibilização das comunidades organizacionais e académicas a esta temática, que contribua para uma compreensão mais abrangente e atual da sua relevância no seio das organizações. A mudança multidimensional de paradigma insurge-se num contexto situacional económico-financeiro estruturalmente debilitado, o que instiga a uma transfiguração dos conceitos e padrões observados até aqui. O empreendedorismo e o perfil comportamental do líder empreendedor assumem assim uma capital importância no processo eficaz de criação de valor: incremental, diferenciador e sustentável. Palavras-chave: Empreendedorismo, perfil do empreendedor, desempenho organizacional, inovação, sustentabilidade, oportunidade.